A Comparative Economics of Farm Machinery Ownership and Hiring for Farming - Parashunath, .; Hiremath, GM (Journal of Agricultural Extension Management, 2018)
Farm mechanization helps to ensure timely field operations to increase productivity, reduce crop losses and improve the quality of grain or produce, increase use of land and other inputs more effectively and increase labour productivity by using labour saving and drudgery reducing devices. At present, in India, tractors are being used for tillage on about 22.78 per cent of the total land area and sowing about 21.30 per cent of total area. Custom hiring service (CHS) is a popular method of gaining short-term control of farm machinery among farmers who do not own them. Custom hiring gained importance mainly due to rise in the cropping intensity and drop in average landholdings. The productivity of major crops is higher on the tractor owning farms due to timely and sufficient availability of tractor services. NetÂ  farm income is higher on tractor owning farms but input costs are low on custom hiring farms. This may be due to the high fixed costs as well as repair and maintenance costs on tractor owning farms. The small and medium tractor hiring farms earned more net income. This shows that it is better for smaller farms to hire in tractor services rather to have their own tractor. On the other hand owning a tractor is economically beneficial for larger farmers